Pemberdayaan Masyarakat Melalui Urban Farming Sebagai Strategi Mitigasi Stunting: Kasus di "Buruan SAE" - Haqi, Muamar; Armansyah, Armansyah (Seminar Nasional Lahan Suboptimal, 2024)
Haqi., M., Armansyah, A. (2024). Community empowerment through urban farming as a stunting mitigation strategy: a case study of "Buruan SAE". In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang  21 Oktober 2024. (pp. 272–280).  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Stunting is one of the main indicators of poor nutritional status in children whose prevalence is still high in various regions in Indonesia, including urban areas. This research examines stunting mitigation strategies through community empowerment in urban agriculture. The focus of this research is urban farming in Bandung, West Java, known as Buruan SAE. The study aimed to was analyze the role of urban agriculture as part of the stunting mitigation strategy. This study examines various urban farming initiatives in Buruan SAE and how they impact local communities in obtaining and consuming nutritious food. This research used a qualitative approach. The results show that Buruan SAE urban farming in Bandung can play an important role in stunting mitigation by increasing families' access to safe, fresh and nutritious food products and providing education on healthy eating and urban farming practices. Urban farming activities also contribute to community empowerment and increase awareness of the importance of nutritious food for a healthy life.